Potassium channels as a potential therapeutic target for trigeminal neuropathic and inflammatory pain - Iwata Koichi; Nakagawa Kazuharu; Kitagawa Junichi; Tsuboi Yoshiyuki; Takeda Mamoru; Matsumoto Shigeji (SAGE Publishing, 2011)
Abstract Previous studies in several different trigeminal nerve injury/inflammation models indicated that the hyperexcitability of primary afferent neurons contributes to the pain pathway underlying mechanical allodynia. Although multiple types of voltage-gated ion channels are associated with neuronal hyperexcitability, voltage-gated K+ channels (Kv) are one of the important physiological regulators of membrane potentials in excitable tissues, including nociceptive sensory neurons. Since the opening of K+ channels leads to hyperpolarization of cell membrane and a consequent decrease in cell excitability, several Kv channels have been proposed as potential target candidates for pain therapy. In this review, we focus on common changes measured in the Kv channels of several different trigeminal neuropathic/inflammatory pain animal models, particularly the relationship between changes in Kv channels and the excitability of trigeminal ganglion (TRG) neurons. We also discuss the potential of Kv channel openers as therapeutic agents for trigeminal neuropathic/inflammatory pain, such as mechanical allodynia.